Tourism Service Marketing Process - Wulan, Nur (International Publisher (YAPENBI), 2022)
The purpose of this study is to find out how the marketing process for tourism services is, to find out what obstacles can hinder the marketing process for tourism services, to find out what solutions are being carried out in overcoming obstacles in the marketing process for tourism services. The research methodology used is descriptive qualitative which aims to describe the conditions and analyze the marketing process of tourism services. In this study, data related to the author's study are sourced from library studies, field studies, and documentation techniques. The results of research on the marketing process of tourism services, the authors can conclude that to understand the products offered to the customer, the company is obliged to provide training on product knowledge to freelance officers. Lack of anticipating price competition at the same level of tourism service class. The distribution of brochures and website updates has not been carried out properly so that customers are less aware of the existence of the tourism travel agency.